Fatores de influência na determinação da composição corporal de frangos de corte obtidos em aparelho de duplo feixe de raio x - Miranda, Nicole de Moraes [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
The objective of this study was to evaluate the influence of the position and number of broilers during the reading in a double X-ray beam (DXA) device on body composition results. We used 12 Cobb500 broiler chicks at 37 days of age, obtained from a commercial hatchery and feed with a diet following the recommendations of the scan. In total, 40 birds were housed in a box with one day of age and had free access to feed and water during the period of 37 days. After this period, all birds were weighed for the selection of 12 individuals with live weight ranging in ± 5% of the average weight of the experimental box. At 38 days, the birds were slaughtered and sent to the imaging laboratory for reading in DXA The response variables were divided into two groups called, 1 – dxa output, without transformation, which includes fat and lean mass, mineral content, and bone density; and 2 24 – output of the processed DXA, which includes the variables fat, protein, water and ash. The treatments were distributed in a completely randomized design. In the comparison of the data without transformation, a factorial scheme (2 positions x 2 amounts of birds) was used in four unbalanced treatments containing 12 replicates of a bird and four replicates of three birds each. For the transformed data, five treatments were used (1- individual open bird, 2- group open bird, 3- individual closed bird, 4- group closed bird and 5-control). The control group was obtained with the results of the chemical analyses of the birds. For the results without transformation there was no significant interaction between the factors position of the bird and the number of birds scanted. However, the position of the bird influenced the values of all variables studied, except for the fat mass, all of which were higher for birds scanted with closed limbs. Body ash did not have a significant effect regardless of the position or number of birds. In the case of body protein, there was a difference in both factors. We can observe that the greatest difference between DXA and chemical analysis occurred when the bird was positioned openly and individually, with a reduction of 56.5 g in the protein value estimated by DXA. The results of the estimated body water among individuals in the open and closed position were different, but there was no difference in relation to the number of birds. The greatest difference in body water was in the open and group position. As a result, DXA underestimated body water results by 318 g. In the results of body lipid, there was no significant difference between birds in the closed and open position. However, all other response variables were affected. It is concluded that for evaluation of body protein, it is recommended to read birds in closed position and in groups. The other results showed a difference between the transformed results of DXA and chemical analyses, evidencing the need for further studies to improve the accuracy and accuracy of the equations used to transform the body composition results obtained in double X-ray beams.

Objetivou-se avaliar a influência da posição e do número de frangos de corte durante a leitura em aparelho de duplo feixes de raios X (DXA) nos resultados de composição corporal. Foram utilizados 12 frangos de corte Cobb500 com 37 dias de idade, obtidos de um incubatório comercial e alimentos com uma dieta seguindo as recomendações da linhagem. No total, 40 aves foram alojadas em box com um dia de idade e tiveram acesso livre a ração e água durante o período de 37 dias. Após esse período, todas as aves foram pesadas para a seleção de 12 indivíduos com o peso vivo variando no máximo ± 5% do peso médio do box experimental. Aos 38 dias, as aves foram abatidas e encaminhadas ao laboratório de imagem para a leitura no DXA. As variáveis respostas foram divididas em dois grupos denominados de, 1 – output do DXA, sem transformação, que inclui massa gorda e magra, conteúdo mineral e densidade óssea; e 2 – output do DXA transformados, que inclui as variáveis gordura, proteína, água e cinzas. Os tratamentos foram distribuídos em um delineamento inteiramente casualizado. Na comparação dos dados sem transformação foi utilizado um esquema fatorial (2 posições x 2 quantidades de aves), em quatro tratamentos desbalanceados contendo 12 repetições de uma ave e quatro repetições de três aves cada. Para os dados transformados, foram utilizados cinco tratamentos (1– ave aberta individual, 2- ave aberta em grupo, 3- ave fechada individual, 4- ave fechada em grupo e 5- controle). O grupo controle foi obtido com os resultados das 23 análises químicas das aves. Para os resultados sem transformação não houve interação significativa entre os fatores posição da ave e número de aves escaneadas. No entanto a posição da ave influenciou os valores de todas as variáveis estudadas, com exceção da massa gorda, todos foram maiores para as aves escaneados com os membros fechados. As cinzas corporais não apresentaram efeito significativo independentemente da posição ou do número de aves. No caso da proteína corporal, existiu diferença nos dois fatores. Podemos observar que a maior diferença entre o DXA e a análise química ocorreu quando a ave foi posicionada aberta e individualmente, apresentando redução de 56.5 g no valor da proteína estimada pelo DXA. Os resultados da água corporal estimada entre indivíduos na posição aberta e fechada foram diferentes, mas não houve diferença com relação ao número de aves. A maior diferença na água corporal foi na posição aberta e em grupo. Com isso, o DXA subestimou os resultados de água corporal em 318 g. Nos resultados de lipídeo corporal, não houve diferença significativa entre aves na posição fechada e aberta. Entretanto, todas as demais variáveis resposta foram afetadas. Conclui-se que para avaliação da proteína corporal, recomenda-se a leitura de aves em posição fechada e em grupo. Os demais resultados demonstraram diferença entre os resultados transformados do DXA e as análises químicas, evidenciando a necessidade de mais estudos para melhorar a acurácia e precisão das equações utilizadas para a transformação dos resultados de composição corporal obtidos em aparelhos de duplo feixe de raios X.
Influence factors in the determination of body composition of brilliant chickens obtained in double x-ray beam apparatus
Keywords: Aves; Composição corporal; Nutrição animal